Best Choice of the Separating Material for Pressure Plate Tests. (November 2015) - Feng, Chi; Feng, Ya; Meng, Qinglin; Janssen, Hans
Abstract: This paper investigates the best separating material for pressure plate tests, choosing from silk cloth, filter paper and cellulose film. Measurements at 3 bar and 12 bar reveal that the influence of separating materials is negligible for autoclaved aerated concrete, while cellulose film is the best for calcium silicate and ceramic brick because of the more reliable results. Repeated tests at 3 bar further advocate cellulose film for the smallest repeatability errors. In conclusion, cellulose film is superior to silk cloth and filter paper as the separating material in pressure plate tests.